Not going to the mainland: queer women's narratives of place in Tasmania, Australia. Issue 8 (3rd August 2021) - Grant, Ruby
Abstract: Within Australian geographies of sexualities, most work centres the urban areas of Sydney, New South Wales, while less is known about queer life in regional and rural Australia. In contrast, this article explores how lesbian, bisexual and queer young women understand and experience identity and place in Tasmania. Using a queer futurities theoretical framework and a qualitative feminist methodology, in this article I examine how narratives of place shape queer Tasmanians' understandings of identity, belonging, and home. Participant narratives of leaving, arriving, and returning to Tasmania reflect dominant rural youth migration patterns, while also providing new insights into how queer young people position Tasmanian space, identities and futures in broader Australian culture. This article draws on recent work in geographies of sexuality to show how Tasmania produces unique sexual identity cultures that influence queer young women's sense of time and place.